2013
DOI: 10.1177/1098612x13497738
|View full text |Cite
|
Sign up to set email alerts
|

Case series of feline panleukopenia virus in an animal shelter

Abstract: The aim of this study was to describe a series of confirmed and suspected cases of feline panleukopenia virus (FPV) and in-contact cats in an adoption-guarantee shelter in an FPV-endemic area by reviewing shelter records over a 10-month period (January-October 2010). Cats were divided into three groups: in-contact group - asymptomatic cats that were housed with a FPV fecal antigen (Ag)-positive cat/kitten as part of a litter group (n = 66); FPV-survivors group (FPV-infected survivors) - tested FPV fecal Ag-pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0
11

Year Published

2016
2016
2025
2025

Publication Types

Select...
4
3
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 14 publications
2
24
0
11
Order By: Relevance
“…In our opinion, clinical evidence suggests that in cats gastrointestinal signs caused by FPV are less common and milder when present, as compared to CPV infection in dogs. In fact, parvoviral infection in dogs historically is known as canine parvoviral enteritis, whereas parvoviral disease in cats traditionally is named feline panleukopenia . Thus, because hypocholesterolemia is also a marker of severity of gastrointestinal signs, it is not surprising that dogs with hypocholesterolemia, and possibly a more severe form of the disease, also have a worse outcome …”
Section: Discussionmentioning
confidence: 99%
“…In our opinion, clinical evidence suggests that in cats gastrointestinal signs caused by FPV are less common and milder when present, as compared to CPV infection in dogs. In fact, parvoviral infection in dogs historically is known as canine parvoviral enteritis, whereas parvoviral disease in cats traditionally is named feline panleukopenia . Thus, because hypocholesterolemia is also a marker of severity of gastrointestinal signs, it is not surprising that dogs with hypocholesterolemia, and possibly a more severe form of the disease, also have a worse outcome …”
Section: Discussionmentioning
confidence: 99%
“…The most common clinical signs are anorexia, lethargy, fever, dehydration, hemorrhagic diarrhea, and vomiting [3]. Diagnosis is made by combining history, clinical findings, and hematologic changes together with detection of FPV or canine parvovirus (CPV) antigen in feces or viral DNA in blood or in feces [1,4]. A recent study on survival and prognostic factors of FPV [5,6] showed that shelter cats without signs of lethargy, with a higher body weight, or higher rectal temperature at admission were more likely to survive.…”
Section: Introductionmentioning
confidence: 99%
“…Feline panleukopenia virus (FPV), or feline parvovirus, is a highly contagious pathogen that can cause severe illness in cats, particularly kittens, with a mortality rate of 50-90%. [1][2][3][4] Feline panleukopenia (FP) infection is important in animal shelters, which frequently house large numbers of un-or under-vaccinated kittens. 3,5 Outbreaks can result in high mortality, euthanasia and shelter closures.…”
Section: Introductionmentioning
confidence: 99%